Recent advances on fatigue of rubber after the literature survey by Mars and Fatemi in 2002 and 2004 - Tee, Yun Lu; Loo, Mei Sze; Andriyana, Andri (Elsevier, 2018)
Subjected to multiaxial mechanical loading and hostile environment, rubber experiences degradation over a period of time. Therefore, it is of utmost importance to prevent failure of rubber components during the service. As highlighted in Mars and Fatemi [Mars, W.V, Fatemi, A., 2002. A literature survey on fatigue analysis approaches of rubbers. Int. J. Fatigue 24, 949–961; Mars, W.V, Fatemi, A., 2004. Factors that affect the fatigue life of rubber: A literature survey. Rubber Chem. Technol. 77, 391–412], a large number of works focused on the durability of rubber. Furthermore, it has been expanding rapidly until today. For this reason, the present work focuses on collecting and analyzing the vast amount of works on fatigue of rubber conducted in the last 15 years since the review of Mars and Fatemi in 2002 and 2004. To this end, three bibliographic databases are consulted: Google Scholar, Scopus and Web of Science. The collected works are analyzed with the objective to identify the current and future trends and needs in the study of rubber fatigue.